A Methods engineering study of Italit Const. & Dev. Corp. - Claudio, Kristine; Rosales, Ryan; Rosario, Michael; Ruiz, Dida Rowena (College of Engineering, 1997)
This study aims to apply the techniques learned in Methods Engineering to an actual industrial setting to improve productivity. The system under study is the production of uPVC pipes of Italit Construction and Development Corporation. The main problems addressed are : lack of emphasis on the intermediate needs of the lant such as the elimination of accumulated rejects and inefficient layout and poor implementation of company policies such as poor working conditions and lack of standard operating procedures. The recommendations of the team are based on the data and results gathered. The recommendations are : install a regrinding method on a permanent basis, improve layout by the removal of unnecessary items in the work area, employment of safety measures and rules on good housekeeping, and establish standard operating procedures.